Are bald men more virile than their well thatched contemporaries?. Issue 11 (16th December 2013) - Sinclair, Rodney D; English, Dallas R; Giles, Graham G
Abstract: Objective: To test the popular assertion that bald men are more virile than their well thatched contemporaries Design, participants and setting: Secondary analysis of data from a case–control study in a community setting between 1994 and 1997 among men below the age of 70 years, using in‐person interviews and categorisation of baldness, with subsequent completion of a questionnaire by the participant. We analysed risk factors for baldness using unconditional logistic regression. Main outcome measures: Baldness; history of ejaculations between the ages of 20 and 49 years; total number of sexual partners. Results: There was no significant association between baldness and the frequency of ejaculations, but bald men were significantly less likely to have had more than four female sexual partners. Conclusions: In the population studied, bald men appear to be no more virile than their well thatched contemporaries.